Crossing Borders: Social-spatial Relations between Brussels and Flemish Brabant - Filip de Maesschalck; Tine De Rijck; Vicky Heylen (Brussels Studies, 2015)
This contribution discusses the moves between the Brussels municipalities and the Brussels periphery in Flemish Brabant. Even in the most recent period, mainly young families moved to the periphery, leading to an impoverishment of Brussels. This observation is not new, but the socio-economic profile of the movers has rarely been examined. This study does so, confirming the perception of movers having higher incomes than the Brussels average. Income variations between the destination municipalities or districts are substantial but the large majority of the movers do have work. The strong increase in the number of movers of non-Belgian origin is a notable evolution. Suburbanization is no longer a concern of middle class individuals of Belgian origin. The number of moves in the other direction is much smaller, but there exists an important commuting flow towards Brussels. This contribution highlights the work commute and the commutes in other, less documented domains: commuting to school and commuting in order to use social services. These flows also are mainly oriented towards Brussels.